Supply Chain Finance: A Potential Tool for Economic Prosperity in African Countries - Franklin, Mballa Fortune; Zhou, Jie (International Journal of Global Economics and Management, 2024)
Supply chain finance (SCF) has emerged as a pivotal tool to encourage economic prosperity, especially in African regions where Small and Medium Enterprises (SMEs) often face significant capital shortages. Small-sized businesses usually struggle to fulfill client’s demands or honor a contract with bigger firms. That is a fact in countries all around the globe, however, this condition is considered more severe in African countries. African countries face challenges in managing global supply chain chains due to government instability, corruption, limited technology use, and low education levels. With the rise of globalization, it has become ever more crucial to transform and stabilize supply chain management in the region. Supply chain finance (SCF) analyzes capital flows in a supply chain, aiming to reduce financing costs and increase efficiency, which has been an overlooked area for a long time. This research was conducted to understand the potential SCF holds regarding improving the economy in African countries.